THE EFFECT OF INTEGRATED THEMATIC LEARNING MODEL ON LEARNING OUTCOMES THE THEORY OF MIDWIFERY CARE COMMUNITY OF DIPLOMA III MIDWIFE STUDENTS - Donna Harriya Novidha (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Introduction: The competence of midwives in the community according to the needs of the community requires a breakthrough in improving the quality of midwifery education. An effective learning process will help students achieve optimal learning outcomes so that competence can be achieved. This study aims to analyze the effect of the integrated thematic learning model on the learning outcomes of midwifery care theory in the community of D-III Midwifery students. Method: The research method used is experimental with a randomized control trial design . The subjects of this study were 79 students of D-III Midwifery STIKes Merangin which were divided into two groups, namely 39 treatment groups and 40 control groups. The treatment group was given learning about community midwifery care in the classroom using an integrated thematic learning model, while the control group was given a conventional learning model. Both groups received the same material and learning time for 6 weeks. After the classroom learning was completed, the theoretical learning outcomes were measured in both groups using a questionnaire. The research data were analyzed using unpaired t -test, Mann-Whitney test and Chi-square test according to the data type . Result: The results of the initial state analysis on the research subjects showed that there was no significant difference between the treatment group and the control group with a p value> 0.05 seen from the GPA (43.6% vs. 52.5%), learning motivation with a median score ( min-max) i.e. 89 (81-99) vs. 89 (77-97), and the initial value of learning theory results with a median score (min-max) at 65 (55-73) vs . 60 (56-74) so ​​that the two groups are equal. After being given the intervention in both groups showed that there were statistically significant differences in learning outcomes in the classroom theory and conventional classes deng thematic an average score ( SB ) ie 8 0, 2 ( 7.4 ) vs . 68 , 6 ( 8.4 ), p <0.05 There is a significant difference at learning achievement outcomes thematic classroom theory with conventional grade 8 2 % vs , 3 to 5% , p <0.05 . Conclution : Result learning achievement theory midwifery care community of students in the class thematic shows a significant achievement compared to students in the class of conventional so Institutions Diploma in Midwifery can use the model of integrated thematic learning in the learning process in the classroom community midwifery care.